Expert Recommendations on Antithrombotic Management of Peripheral Artery Disease: Perspectives from Indian Interventional Radiologists - Kola, Balaji Patel; Yadav, Ajit K.; Keshava, Shyamkumar N.; Pant, Rochan; Gorsi, Ujjwal; Warawdekar, Gireesh Mukund; Sheorain, Virender Singh Kapoorsingh; Bansal, Nikhil; Choudhury, Shuvro Roy; Halbe, Swatee; Ukirde, Vivek Kisan; Gupta, Arun; Kumar, Lijesh; Veettil, Rohith Puthan; Kulkarni, Suyash (Journal of Clinical Interventional Radiology ISVIR, 2025)
Peripheral artery disease (PAD) imposes a heavy burden of major adverse cardiovascular events (MACE) that are associated with considerable mortality and morbidity and major adverse limb events (MALE) (e.g., thrombectomy, revascularization, amputation) that can substantially impact patients' daily functioning and quality of life. Epidemiological studies have indicated that PAD is an underdiagnosed disease in India, and its associated risk factors remain inadequately controlled. Antithrombotic therapy for PAD is underutilized in India. Revascularization procedures are done in acute or advanced stages. While such invasive strategies are effective in some patients with PAD, these strategies are costly and carry risks, and many patients are not amenable to invasive therapy, especially in low-resource settings like in India. In recent years, dual pathway inhibition (DPI) has emerged as a promising approach to improve the treatment of coronary artery diseases and represented a long-awaited major advancement for the medical treatment of PAD, as demonstrated by the Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) and Vascular Outcomes Study of ASA (acetylsalicylic acid) Along with Rivaroxaban in Endovascular or Surgical Limb Revascularization for PAD (VOYAGER-PAD) trials. DPI with rivaroxaban 2.5 mg twice daily + aspirin 100 mg once daily can be used to decrease the risk of MACE or cerebrovascular events and MALE, in PAD patients without high bleeding risk. Clinical evidence, clinical expertise, and real-world practice were integrated to form expert opinions and a clinical algorithm for using DPI as antithrombotic management in patients with PAD. The expert opinions and algorithms can be adopted not only by interventional radiologists in India involved in the clinical management of patients with PAD but also by vascular surgeons and general practitioners in rural areas, aiming to improve the totality of PAD patient care in India.
Keywords: dual pathway inhibition; revascularization; peripheral artery disease; rivaroxaban; antithrombotic therapy; major adverse limb events